2011
DOI: 10.1128/iai.05459-11
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-1 Activation of Interleukin-1β (IL-1β) and IL-18 Is Dispensable for Induction of Experimental Cerebral Malaria

Abstract: Malaria infection is initiated by sporozoite invasion of hepatocytes and asexual reproduction of liver stages, processes that are regarded to be "clinically and diagnostically silent." Merozoites, which egress from hepatocytes, infect erythrocytes in periodic cycles and induce disease. How the host innate immune system contributes to disease outcomes and to the induction of effector cells during malaria remains unclear. Likewise, how the initial liver stages may shape responses to blood-stage parasites is unkn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
58
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 51 publications
5
58
1
3
Order By: Relevance
“…3C). In agreement with published data (14), concentrations of IL-6, IL-10, IFN-␥, MCP-1, and TNF-␣ (Fig. 3D to H) were significantly increased during the course of infection in WT mice, and infected Card9 Ϫ/Ϫ mice had comparable levels of these cytokines.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…3C). In agreement with published data (14), concentrations of IL-6, IL-10, IFN-␥, MCP-1, and TNF-␣ (Fig. 3D to H) were significantly increased during the course of infection in WT mice, and infected Card9 Ϫ/Ϫ mice had comparable levels of these cytokines.…”
Section: Resultssupporting
confidence: 80%
“…Consistent with previous findings (14), both sporozoiteinfected WT and Card9 Ϫ/Ϫ mice succumbed to infection with a mean survival of 7 days. These animals displayed neurological signs associated with ECM, such as ataxia, paralysis, convulsion, or coma (Fig.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…However, whether these TLRs shape the immune response during malaria infection in vivo is a matter of debate. For example, TLR2 deficiency was reported to confer protection from CM in at least two studies (19,36) but was found to have no effect in others (19,27,28). These ambiguous results suggest that more quantitative approaches may offer additional insights into the roles of individual TLRs in sensing infection.…”
mentioning
confidence: 97%
“…In addition, a MYD88-dependent but TLR9-independent pathway appears to contribute to immunopathology in the P. berghei ANKA model of CM. Although conflicting data exist (27), several studies agree that Myd88 Ϫ/Ϫ mice exhibit decreased production of proinflammatory cytokines and improved survival compared to wild-type mice during infection with P. berghei ANKA (19,28,35,36), whereas TLR9-deficient mice exhibit a milder defect in cytokine production than do Myd88 Ϫ/Ϫ mice (19,28) and may not be protected from CM to the same extent (discussed in reference 28, but see reference 19). Together, these data suggest that other MYD88-dependent innate sensors may cooperate with TLR9 in host recognition of Plasmodium infection.…”
mentioning
confidence: 99%